Sacral Dysgenesis Associated with Terminal Deletion of Chromosome 7 (q36-qter) - Pen-Hua Su; Jia-Yuh Chen; Suh-Jen Chen; Teng-Fu Tsao; Yu-Jie Lai (Elsevier, 2008)
We report on the clinical, cytogenetic, and imaging findings in a patient with a 7q terminal deletion. The 11-year-old girl had mental retardation, microcephaly, a distinctive face, relatively small hands and feet, and sacral dysgenesis. High resolution GTG banding (550-850 bands) showed a 7q terminal deletion. A detailed evaluation of associated malformations and the overall clinical picture should be taken into account when identifying the underlying diagnosis in cases of sacral dysgenesis with mental retardation.